2008
DOI: 10.1186/1751-0147-50-19
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antimicrobial resistance among bacterial pathogens and indicator bacteria in pigs in different European countries from year 2002 – 2004: the ARBAO-II study

Abstract: Background: The project "Antibiotic resistance in bacteria of animal origin -II" (ARBAO-II) was funded by the European Union (FAIR5-QLK2-2002-01146) for the period 2003-05. The aim of this project was to establish a program for the continuous monitoring of antimicrobial susceptibility of pathogenic and indicator bacteria from food animals using validated and harmonised methodologies. In this report the first data on the occurrence of antimicrobial resistance among bacteria causing infections in pigs are report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 17 publications
6
58
1
Order By: Relevance
“…The growing interest in this emerging pathogen is reflected by recent whole-genome sequencing studies of selected isolates directed at elucidating the occurrence and evolution of the genetic determinants of its pathogenicity and drug resistance (7,18,43). High rates of tetracycline resistance have been reported in both human and pig isolates of S. suis (17,22,41,44). Before our report (23), tet(M) and tet(O) were the only tetracycline resistance determinants identified in S. suis (8,35,38,42); quite recently, tet(L) (18), mosaic tet(O/W/32/O) (25), and tet(W) itself (25,43) have also been reported.…”
Section: Tet(w)mentioning
confidence: 99%
“…The growing interest in this emerging pathogen is reflected by recent whole-genome sequencing studies of selected isolates directed at elucidating the occurrence and evolution of the genetic determinants of its pathogenicity and drug resistance (7,18,43). High rates of tetracycline resistance have been reported in both human and pig isolates of S. suis (17,22,41,44). Before our report (23), tet(M) and tet(O) were the only tetracycline resistance determinants identified in S. suis (8,35,38,42); quite recently, tet(L) (18), mosaic tet(O/W/32/O) (25), and tet(W) itself (25,43) have also been reported.…”
Section: Tet(w)mentioning
confidence: 99%
“…This humanveterinary information gathering initiative introduced scientific rigour to the surveillance process, addressing many of the variables that could otherwise confound interpretation of data (Wallmann et al 2003). Within a veterinary framework, Hendriksen et al (2008aHendriksen et al ( , 2008b) surveyed resistance across Europe among bacterial pathogens and indicator bacteria for pigs and cattle. While their work did not incorporate harmonisation efforts into the data collection process, it did provide a positive step forward towards the creation of national surveillance schemes.…”
Section: Monitoring Programmes: Points To Considermentioning
confidence: 99%
“…S. suis is an important zoonotic pathogen that leads to economic losses and severe invasive diseases in humans, with meningitis being the most common clinical presentation [4,12,21]. It has been reported that 421 isolates of S. suis from clinically healthy sows in China exhibited high level resistance to commonly used antibiotics, including tetracycline, sulfisoxazole, clindamycin, erythromycin and trimethoprim/sulfamethoxazole [10,26,28]. Novel antibiotics can be developed, but the pathogens ultimately become resistant to such drugs.…”
Section: Introductionmentioning
confidence: 99%